Pengaruh Sistem Keuangan Desa (Siskeudes) dan Partisipasi Masyarakat Terhadap Kualitas Laporan Keuangan Pada Desa-desa di Kecamatan Bulango Utara Kabupaten Bone Bolango Provinsi Gorontalo - Taufik Satriawan Parenrengi; Harun Blongkod; Ikhlas Ul Aqmal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of the village financial system (siskeudes) and community participation on the quality of financial reports. This study was conducted in villages in North Bulango District, Bone Bolango Regency, Gorontalo Province using quantitative methods. Data was collected through questionnaires. The analysis techniques used include validity tests, reliability tests, and descriptive analysis. The data collection process uses a purposive sampling technique or samples with certain criteria, namely villages that have used the siskeudes application for at least one year with a total sample of 120 respondents in nine different villages, namely Boidu, Suka Damai, Bandungan, Tupa, Tuloa, Lomaya, Kopi, Bunuo, Longalo, in the North Bulango District Area. The data analysis technique in this study uses Structural Equation Modeling (SEM) or Structural Equation Model which is operated through the AMOS 24 program. The results of this study show that the village financial system has no influence on the quality of financial reports. On the contrary, public participation has an influence on the quality of financial reports. However, simultaneously these two independent variables contribute significantly to the quality of financial statements.